Analysis Of The Impact Of Cyberbullying Through The Instagram Story Feature On The Mental Health Of Generation Z Students In Denpasar - Sahri Aflah Ramadiansyah; Ni Putu Yunita Anggreswari; Ni Made Nila Widya Puspa Dewi; Nuning Indah Pratiwi (Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the impact of cyberbullying through the Instagram Story feature on the mental health of Generation Z students in Denpasar. The rapid advancement of technology and the increasing use of social media have significantly changed the patterns of communication and social interaction among young people. Instagram, as one of the most popular platforms among Gen Z, offers the Story feature that allows users to share daily activities quickly and openly. However, this convenience is often misused for negative actions such as ridicule, sarcasm, or the spread of harmful information. This research employs a Systematic Literature Review (SLR) method by examining various relevant previous studies. The findings indicate that cyberbullying through Instagram Story can trigger psychological problems such as stress, anxiety, low self-esteem, and depression. Moreover, social pressure to appear perfect on social media exacerbates students’ mental health conditions. Nevertheless, Instagram also has positive potential when used wisely as a medium for self-expression, information sharing, and strengthening social connections. Therefore, increasing digital literacy, promoting ethical social media behavior, and encouraging the active role of universities and the government are essential to create a healthy and safe digital environment for the younger generation